Knowledge, attitude, and practices of the community toward dengue fever in Shabwah Governorate, Yemen: a descriptive study - Mohammed Ali Saghir; Waled A. M. Ahmed; Mustafa Mohammed Abdullah Dhaiban; Murwan Eissa Osman; Naif Izzatullah Abduljabbar (SpringerOpen, 2022)
Abstract Background In Yemen, dengue fever (DF) is a widespread, locally endemic infectious disease, with high morbidity and mortality which mainly affects impoverished regions. Thus, this study aims to evaluate the knowledge, attitudes, and behaviors of the Shabwah community in Yemen regarding DF characteristics and prevention. Methods The present study is a cross-sectional community-based study conducted in Shabwah Governorate, Yemen, between June 2021 and November 2021. Simple random sampling was used to select the sample (n = 370), and a validated closed-ended questionnaire was used to collect data. Results In total, 370 individuals participated in this study; most respondents were female (N = 247, 66.8%), and more than half (N = 214, 57.8%) were younger than age 30. More than 50% of the population had completed a primary or secondary school, while approximately 33.03% of them were illiterate. Furthermore, more than half (53.5%) of the population had good knowledge of DF, while most of those educated at a university level (64.1%) had good attitude toward DF. Most of the population (68.4%) had good practice toward DF. Moreover, participants with a university level education, followed by those who completed secondary school, had significantly higher knowledge and practice scores than primary school and illiteracy (P = 0.05). Conclusion The results of the study indicate that the residents of Yemen's Shabwah Governorate are well-informed about the symptoms and signs of DF, have a positive attitude toward the disease, and employ appropriate preventive measures. Health education via various media should be mandated to increase community awareness and dispel misconceptions about DF.